Hypoxia ameliorates maternal diet‐induced insulin resistance during pregnancy while having a detrimental effect on the placenta. Issue 9 (10th May 2022) - Sissala, Niina; Myllymäki, Elisa; Mohr, Florian; Halmetoja, Riikka; Kuvaja, Paula; Dimova, Elitsa Y.; Koivunen, Peppi
Abstract: Maternal overweight/obesity contributes significantly to the development of gestational diabetes, which causes risks to both mother and fetus and is increasing sharply in prevalence worldwide. Since hypoxia reprograms energy metabolism and can alleviate weight gain, adiposity, insulin resistance (IR), and dyslipidemia, we set out to study the potential of sustained reduced ambient oxygen tension (15% O2 ) during pregnancy for alleviating the detrimental effects of diet‐induced IR in C57Bl/6N mice, taking normal chow‐fed and normoxia (21% O2 ) groups as controls. Our data show that hypoxic intervention reduced maternal weight gain, adiposity, and adipose tissue inflammation, and ameliorated maternal glucose metabolism and IR during gestation in diet‐induced IR relative to normoxia. Where diet‐induced IR reduced maternal hemoglobin and increased serum erythropoietin levels, hypoxic intervention compensated for these changes. Diet‐induced IR reduced fetal growth in normoxia, and even more in hypoxia. Hypoxic intervention reduced liver weight gain during pregnancy in the dams with diet‐induced IR, maternal liver weight being positively associated with embryo number. In case of diet‐induced IR, the hypoxic intervention compromised placental energy metabolism and vascularization and increased end‐pregnancy placental necrosis. Altogether, these data show that although hypoxic intervention mediates several beneficial effects on maternal metabolism, the combination of it with diet‐induced IR is even more detrimental to the placental and fetal outcome than diet‐induced IR alone. Abstract : In a mouse model, exposure to hypoxic environment for the duration of pregnancy reduced weight gain, improved glucose tolerance, and alleviated insulin resistance of dams with diet‐induced obesity. Placental vascularization, which supports fetal development and growth, was decreased by hypoxic intervention in dams with diet‐induced obesity. Prolonged hypoxia during pregnancy conveys several beneficial effects on maternal metabolism but in combination with diet‐induced obesity is detrimental to the feto‐placental unit and therefore not as such a suitable method for treatment of gestational diabetes.